Potency of Garlic Extract Against Koi Herpesvirus (KHV) in Common Carp - Sri Nuryati; D. Puspitaningtyas; D. Wahjuningrum (Jurnal Akuakultur Indonesia)
Prevention of koi herpesvirus (KHV) infection using chemicals or medicines was ineffective way.  In this study garlic extract was used to prevent KHV infection.  Virus suspension of 0.1 ml and garlic extract of 0.1 ml in different dosage, i.e., 100, 200 and 300 ppt, was injected into common carp body.  Hemoglobin concentration, red and white blood cell numbers, and leukocyte number were counted.  The results of study showed that administration of 300 ppt of garlic extract could produce higher survival rate (67.5%), good blood parameters and clinical symptoms compared to other treatments.